2018
DOI: 10.1371/journal.pone.0194592
|View full text |Cite
|
Sign up to set email alerts
|

Changes in maize transcriptome in response to maize Iranian mosaic virus infection

Abstract: BackgroundMaize Iranian mosaic virus (MIMV, genus Nucleorhabdovirus, family Rhabdoviridae) causes an economically important disease in maize and other gramineous crops in Iran. MIMV negative-sense RNA genome sequence of 12,426 nucleotides has recently been completed. Maize Genetics and Genomics database shows that 39,498 coding genes and 4,976 non-coding genes of maize have been determined, but still some transcripts could not be annotated. The molecular host cell responses of maize to MIMV infection including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Another group of genes, which expression were altered, in viral infection was the photosynthesis genes as: phytochrome B, calmodulin binding and ferredoxin-NADP root (fnr1). This is because the induction of these genes may be related to yellow stripe and chlorosis symptoms on the leaves (Ghorbani et al 2018a). Here again we can verify the importance of studies using transcriptomic tools for the understanding of different mechanisms of the virus-plant interaction.…”
Section: Nucleorhabdovirus Genusmentioning
confidence: 73%
See 1 more Smart Citation
“…Another group of genes, which expression were altered, in viral infection was the photosynthesis genes as: phytochrome B, calmodulin binding and ferredoxin-NADP root (fnr1). This is because the induction of these genes may be related to yellow stripe and chlorosis symptoms on the leaves (Ghorbani et al 2018a). Here again we can verify the importance of studies using transcriptomic tools for the understanding of different mechanisms of the virus-plant interaction.…”
Section: Nucleorhabdovirus Genusmentioning
confidence: 73%
“…Analyses about the viral-host interaction were also perfomed. Maize plants infected and not infected by MIMV displayed different metabolic profiles modulated by MIMV infection, including biosynthesis of secondary metabolites, proteasome, protein processing in endoplasmic reticulum, photosynthesis and two pathways with significant roles in pathogen defense: fatty acid (FA) metabolism and degradation (Ghorbani et al 2018a). These pathways are important because have been showed that FA are able to modulate the basal effector-triggered and systemic immunity in plants, besides to be biosynthetic precursors for cuticular components or the phytohormone jasmonic acid (Kachroo and Kachroo 2009).…”
Section: Nucleorhabdovirus Genusmentioning
confidence: 99%
“…Contaminating genomic DNA was removed during mRNA purification. Whole transcriptome RNA was enriched by Macrogen by depleting ribosomal RNA, and six independent cDNA libraries were prepared using poly(A) enrichment from 3 plants each of MIMV-infected and non-infected maize [27].…”
Section: Library Construction Sequencing and Rna-seq Data Analysismentioning
confidence: 99%
“…RNA-Seq has been used to find insights in several plant-virus interactions, including model plants such as Arabidopsis thaliana (Sun et al, 2016;Wu et al, 2016), plants of agronomical importance such as Oryza sativa (Blazquez et al, 2013;Wong et al, 2015), Zea mays (Chakrabarty et al, 2018), Manihot esculenta (Fang et al, 2014;Amuge et al, 2017;Anjanappa et al, 2018), Solanum tuberosum (Goyer et al, 2015;Stare et al, 2017) and tropical fruits such as C. papaya (Madroñero et al, 2018). However, to date (04-10-2019), a Google Scholar search, the NCBI PMC database, and the Web of Science using the queries "plant", "virus", "interaction", "transcriptome", "RNA-Seq", and "Colombia" with different combinations did not yield any results for plant-virus interactions research developed in Colombia.…”
Section: Ngs In Transcriptomics To Elucidate Plant-virus Interactionsmentioning
confidence: 99%